THE STRATEGIES FOR LOCAL WISDOM-BASED PREACHING IN GUNUNG SITOLI, NIAS - Yusnita Hasibuan (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2024)
The Nias community is generally known for being predominantly Christian, a religion they have embraced for a very long time. However, not many are aware that Islam has been present on the island of Nias for a longer time, introduced by immigrants from Aceh and Minang, although not fully accepted by the Nias community. Local wisdom encompasses the unique knowledge, values, norms, and traditions of the local population. In this research, two primary strategies for comprehensive preaching delivery are the use of the local language and empowering Nias youth and local leaders. The use of the local language is deemed effective because the majority of the local population primarily uses it in their daily activities, including sermons, Friday khutbah, and various other religious events. Furthermore, translating major religious texts such as the Quran and Hadith into the local language facilitates better understanding of the preaching. The use of the local language is also conveyed in written form in the Nias language. The research methodology employed is qualitative, involving data collection through observation, interviews, participation, surveys, document analysis, and documentation. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions, with source triangulation used in this research. The research results indicate that the strategy for global preaching through Nias local wisdom involves in-depth research on Nias culture, participation in Nias community activities and local traditions, as well as providing training and support to local figures to become preaching leaders.